Production of biochars derived from sewage sludge and orange peels - Lima, Larissa Firmino de; Monteiro, Victória Regina Celso; Barquilha, Carlos Eduardo Rodrigues; Braga, Maria Cristina Borba (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The increasing accumulation of waste in the environment has several environmental and public health impacts. In contrast, the circular economy emerges as a model that seeks the return of waste to the production chain. An alternative for the reinsertion of these materials to the production cycle is their conversion into biochar by the pyrolysis process. Thus, this study aims to produce, perform the initial characterization and compare biochars obtained from two different matrices: sludge from sewage treatment plants and orange peels. The sludge samples were pyrolyzed at 450 °C (BL450) and 650 °C (BL650). While the orange peel biochars were produced at 400 °C (BC400) and 600 °C (BC600). Yields were determined and analyzes of scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) were also performed. The yields obtained were 32% (BC400), 28% (BC600), 46% (BL450) and 38% (BL650). The presence of pores was identified in the BC400 and BC600 SEM micrographs. However, for the BL450 and the BL650 samples, heterogeneous and asymmetric surfaces were observed. From the EDX analysis the absence of trace metals and the presence of compounds potentially beneficial to the soil and plants were found, which can act as binders in the adsorption process. In addition, due to their mostly carbonaceous composition, biochars are resistant to decomposition and can contribute to the carbon sequestration process. The yields obtained indicate a reduction of the mass of waste, which can be advantageous for handling and transportation. As a result, the production of biochar from non-conventional materials, such as sewage sludge and orange peels, can be seen as an attractive alternative for waste management, since it assists the reintroduction of these materials in the production chain, according to the concept of circular economy.